Evaluation of methodologies for counting of ticks in the parasitic life phase - Rodríguez, María Inés (2021)
The study aimed to compare the accuracy of tests or methods for counting engorged ticks in cows reared under extensive production systems. In total, 49 adult cows of the Criollo Ñeembucú, Brown Swiss, Brangus and Nelore genotypes were used during the summer in March 2019. Several body regions were reviewed sequentially using the indirect visual method, palpatory and finally the direct method, defined the latter as the gold standard. To estimate the validity and reliability indicators, comparison of the behavior of the receiver operating characteristics curves (ROC) and concordance tests, the Epidat 3.1 program for epidemiological analysis of tabulated data was used. The sensitivity and negative predictive value were markedly higher for the palpatory test. The poor value of the Kappa index revealed that the agreement between the indirect and direct visual method was due to random (p=0.2097). In the palpatory method, the ROC curve showed a larger area compared to the indirect visual method. The results of the homogeneity test of the ROC areas revealed that the difference in the efficacy of both tests was highly significant (p<0.01), proving the limited usefulness of the indirect visual method applied to the count of engorged ticks in the parasitic phase, as opposed to the palpatory method.